Escalation Ladder and the Game of Chances in the Ukraine war of 2022 - Nycz, Grzegorz (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
The paper refers to the most recent developments during the 2022–2023 Ukraine war, analysed from the perspective of selected insights derived from deterrence studies, most notably the escalation ladder. The reason for the publication is to point out dangerous escalatory steps in the context of Putin’s Russia-Ukrainian war, including the abolishment of strategic arms control and tactical nuclear weapons deployment in the EU neighbourhood. V. Putin’s regime’s steps towards seizure or control of Ukraine’s largest nuclear power plant were discussed internationally as a severe humanitarian hazard. The pre-1989 deterrence debate could add a vital research perspective missing in the analytic frames of the New Cold War. Notably, the developments of the 2023 conduct of the Ukraine war with the support of the West countering the impact of a nuclear crisis scenario (tactical arsenal employment) could be analysed in the context of earlier concepts of limited war (1960s), as well as further elaborations on conditions of mutual vulnerability.